The Insecure City (2016)
Urban anthropologist Kristin Monroe takes urban anthropology in a new and meaningful direction—the story of traffic in the Middle East, focusing on Beirut. As bombs reappeared recently following an impasse between competing political groups and their international backers, residents of the city were forced to contend with many forms of insecurity, forging their lives amid a contentious, often violent, political and economic landscape. Images and headlines in the news media tracked the dramatic events that characterized this unstable situation, but they did not provide a picture of what ordinary life was like for urban dwellers in a city terrorized by political sectarianism and the treat of bombs. The Insecure City is an ethnographic exploration of the experiences of moving through Beirut. Driving is characterized by precariousness, the anticipation of violence, and the constant presence of class, political, and state power.